Peramalan Penjualan dan Keuntungan Sayuran Hidroponik (Studi Kasus di CV. Mulyana Reksa Tani (Amatta Farm), Karawang, Jawa Barat) - Rulita Ramadanti; Abubakar Abubakar; Luthfi Nur’azkiya (Jurnal Ilmiah Wahana Pendidikan, 2022)
Mulyana Reksa Tani (Amatta Farm) is a company that produces hydroponic vegetables located in Karawang Regency, West Java Province. The types of vegetables cultivated by Amatta Farm include pak choy, kale, and green spinach. These three types of vegetables have very fluctuating sales figures. The purpose of this study was to calculate the average sales and profit forecast of hydroponic vegetables pak choy, kale, and Amatta Farm green spinach for the next 12 months. The research methods used are descriptive analysis and case studies. This study uses primary and secondary data. Primary data collection was conducted using interview and questionnaire techniques. Secondary data was obtained from the Ministry of Agriculture and the Ministry of Health. The sampling technique was purposive sampling. The analysis technique used is the decomposition multiplicative Forecasting Method and profit calculation. The results of sales and profit forecasting show that the average sales of pak choy are 449,749 packs, kale is 374,894 packs, green spinach is 463,157 packs, and the average profit for pak choy is Rp3.489.144, kale is Rp2.864.749, and green spinach is Rp3.602.645.